Gender equity in computer science through computing in the arts – a six-year longitudinal study. Issue 3 (3rd July 2018) - Bares, William; Manaris, Bill; McCauley, Renée
ABSTRACT: Computing in the Arts (CITA) is an interdisciplinary Bachelor of Arts degree program, which integrates computer science with art theory and practice. We present a 6-year study that explores the impact of the CITA degree on broadening participation. We find that CITA attracts a different student population than traditional computer science degrees. We find that it attracts and retains almost twice as many female students as a traditional computer science degree. Finally, we find that it graduates approximately equal numbers of female and male students. The CITA curriculum maintains its strong computer science character, as it contains several core computer science courses and traditional upper-level computer science courses. We introduce the CITA curriculum model, which combines computer science courses, art courses and several structured synthesis experiences. We show that creating a CITA-like degree is fairly inexpensive, as the curriculum mostly reuses existing courses.